The Effect of Be Co‐Doping on Luminescence Properties of Gd3Al3Ga2O12:Ce Glass Ceramics. Issue 13 (14th May 2022) - Tratsiak, Yauhen; Trusova, Ekateryna; Buryi, Maksym; Babin, Vladimir; Dominec, Filip; Hájek, František; Malashkevich, Georgii
Abstract : The glass‐ceramics (GC) of gadolinium aluminum gallium garnets with the expected composition of Gd3 Al3 Ga2 O12 :Ce and Gd3 Al3 Ga2 O12 :Ce, Be (GAGG:Ce and GAGG:Ce, Be, respectively) are fabricated by crystallization from the Gd2 O3 –Al2 O3 –Ga2 O3 –CeO2 –SiO2 –BeO (Gd:Ga:Al ratio is close to 3:2:3) glasses. The influence of Be 2+ co‐doping (including doping level) on the luminescent properties of the GAGG is demonstrated. In particular, Be co‐doping results in the suppression of the Ce 3+ ‐related radioluminescence (RL) and as a consequence, the light yield is lowered as well. The conclusion is made that Be 2+ creates effective electron or hole trapping centers. Abstract : The article is about the glass‐ceramics form of Gd3 Al3 Ga2 O12 :Ce and Gd3 Al3 Ga2 O12 :Ce, Be, gadolinium aluminum gallium garnets. Be 2+ co‐doping affects the luminescent properties of Ce 3+ in these materials by the suppression of light yield. Moreover, the decay time of the photoluminescence (PL) decreases upon beryllium content. These observations lead to the conclusion of the effective beryllium‐based charge trapping centers' existence.